About Plural Morphology and Game Animals: from Old English to Present-Day English - Fabienne Toupin (Lexis: Journal in English Lexicology)
My focus here will be on those animal names which never (e.g. deer) or occasionally (e.g. herring) take the -s suffix in the plural in Present-Day English. After a detailed presentation of these names (§1), I will try to show (§2) that they form a lexical category in Guiraud’s sense, that is, a non-arbitrary set of nouns with common features at the level both of the signified and of the signifier, and constituting, from a diachronic perspective, a matrix having enabled membership of the category to develop until today. I will then try to explain why this category resisted analogical extension of the -s plural marker, by bringing in the culture of Anglo-Saxon England and the very special status of a group of animals in the culture in question (§3). My conclusion (§4) will stress that multicausality is at work in that resistance to analogy, the cultural factor put forward in §3 being the main explanation. I will eventually explain how these animal names fit into the traditional description of English nouns, and then into Culioli’s speaker-centered theory, known as the Théorie des Opérations Prédicatives et Enonciatives.